Plant Mediated Green Synthesis and Antiviral Activity of Gold and Copper Nanoparticles using Malva parviflora L. Leaf Extract - Seyedeh Raana Charghani; Saadat Rastegarzadeh; Parzhak Zoufan; Seyedeh Elham Rezatofighi (Nanochemistry Research)
In this study, a facile and eco-friendly method was developed for synthesizing gold and copper nanoparticles (AuNPs and CuNPs) using the ethanolic extract of Malva parviflora L., which acts as a reducer and stabilizer. The leaf ethanolic extract of Malva parviflora L. was prepared using an ultrasound-assisted extraction method. The obtained extract is capable of synthesizing red-purple colored AuNPs and green colored CuNPs at ambient conditions. The characterizations of the nanoparticles were carried out using UV–Vis spectrophotometry, transmission electron microscopy (TEM), particle size analysis (PSA), energy dispersive X-ray (EDX) and zeta potential. The antiviral activity of the compounds was evaluated by measuring the viability of the infected cells by a 3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) assay. The TEM images showed that highly dispersed spherical-shaped AuNPs with sizes less than 20 nm and rod-shaped CuNPs with a length of 82 nm and a width of 12 nm were synthesized. The effect of different variables on the biosynthesis and plasmon absorbance of AuNPs and CuNPs was studied. The results indicat that an intensified plasmon absorbance band of AuNPs and CuNPs was observed in alkaline and acidic media, respectively. Although CuNPs have more cytotoxicity than AuNPs, they are more effective at killing viruses. Additionally, ethanolic extract showed significant antiviral activity at non-cytotoxic concentrations.